The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ajim.22230
|View full text |Cite
|
Sign up to set email alerts
|

Do psychosocial working conditions modify the effect of depressive symptoms on long‐term sickness absence?

Abstract: Psychosocial working conditions did not modify the effect of depressive symptoms on LTSA. The results, however, need to be interpreted with caution, as we cannot rule out lack of exposure contrast and non-differential misclassification of the exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…The seriousness of the stress condition in the form of number of days on sick leave, being on full-time sick leave, GSI, and most pronounced work ability index was also significantly associated with RTW. A recent Danish paper has reported similar results on the association between depressive symptoms and long-term sickness absence, but in that study poor psychosocial work environment did not predict sickness absence [ 23 ]. However, the psychosocial work environment was assessed by the use of unit level aggregated measures on work environment.…”
Section: Discussionmentioning
confidence: 84%
“…The seriousness of the stress condition in the form of number of days on sick leave, being on full-time sick leave, GSI, and most pronounced work ability index was also significantly associated with RTW. A recent Danish paper has reported similar results on the association between depressive symptoms and long-term sickness absence, but in that study poor psychosocial work environment did not predict sickness absence [ 23 ]. However, the psychosocial work environment was assessed by the use of unit level aggregated measures on work environment.…”
Section: Discussionmentioning
confidence: 84%
“…There is consistent evidence that higher perceived job demands combined with low job control is related with SA of workers with CMD [ 31 , 33 , 34 , 37 , 43 , 51 , 55 , 63 ]. A job with high decision latitude can largely neutralize the risk of high job demands.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research on the interrelation between psychosocial working conditions, mental health and work ability has focused on overall working populations aged between 18 and 67 years. Those studies have not observed significant interactions between mental health and psychosocial working conditions and rather pointed to independent and additive effects on work ability (Hjarsbech et al 2013;Leijon et al 2017;Munir et al 2011). To the best of our knowledge, similar research that specifically focused on employees of the Baby Boom generation is missing.…”
Section: Introductionmentioning
confidence: 95%